The Challenge of Affluence: Interview with Avner Offer. - Offer, A (2007)
Why do rising incomes not make people happier? Some argue that it is because we quickly become accustomed to our new acquisitions. Others would say that it is because relative status is the goal, not the material acquisitions themselves. But Avner Offer opines it is because we have a difficult time postponing gratification. This is an intriguing notion, one of many in his new book.